Glycogen as an advantageous polymer carrier in cancer theranostics: Straightforward in vivo evidence - Gálisová, Andrea; Jirátová, Markéta; Rabyk, Mariia; Sticová, Eva; Hájek, Milan; Hrubý, Martin; Jirák, Daniel (Scientific reports, 2020)
As a natural polysaccharide polymer, glycogen possesses suitable properties for use as a nanoparticle carrier in cancer theranostics. Not only it is inherently biocompatible, it can also be easily chemically modified with various moieties. Synthetic glycogen conjugates can passively accumulate in tumours due to enhanced permeability of tumour vessels and limited lymphatic drainage (the EPR effect). For this study, we developed and examined a glycogen-based carrier containing a gadolinium chelate and near-infrared fluorescent dye. Our aim was to monitor biodistribution and accumulation in tumour-bearing rats using magnetic resonance and fluorescence imaging. Our data clearly show that these conjugates possess suitable imaging and tumour-targeting properties, and are safe under both in vitro and in vivo conditions. Additional modification of glycogen polymers with poly(2-alkyl-2-oxazolines) led to a reduction in the elimination rate and lower uptake in internal organs (lower whole-body background: 45% and 27% lower MRI signals of oxazoline-based conjugates in the liver and kidneys, respectively compared to the unmodified version). Our results highlight the potential of multimodal glycogen-based nanopolymers as a carrier for drug delivery systems in tumour diagnosis and treatment.
Keywords: lékové transportní systémy; Animals; Antineoplastic Agents; nádory; teranostická nanomedicína; protinádorové látky; krysa rodu Rattus; glykogen; Drug Delivery Systems; Neoplasms; Theranostic Nanomedicine; Cell Line, Tumor; nádorové buněčné linie; Glycogen; zvířata; Rats